Factors affecting the potential for posterior bony impingement after total hip arthroplasty. (September 2017) - Shoji, T.; Yamasaki, T.; Izumi, S.; Murakami, H.; Mifuji, K.; Sawa, M.; Yasunaga, Y.; Adachi, N.; Ochi, M.
Abstract : Aims: Our aim was to evaluate the radiographic characteristics of patients undergoing total hip arthroplasty (THA) for the potential of posterior bony impingement using CT simulations. Patients and Methods: Virtual CT data from 112 patients who underwent THA were analysed. There were 40 men and 72 women. Their mean age was 59.1 years (41 to 76). Associations between radiographic characteristics and posterior bony impingement and the range of external rotation of the hip were evaluated. In addition, we investigated the effects of pelvic tilt and the neck/shaft angle and femoral offset on posterior bony impingement. Results: The range of external rotation and the ischiofemoral length were significantly lower, while femoral anteversion, the ischial ratio, and ischial angle were significantly higher in patients with posterior bony impingement compared with those who had implant impingement (p < 0.05). The range of external rotation positively correlated with ischiofemoral length (r = 0.49, p < 0.05), and negatively correlated with ischial length (r = -0.49, p < 0.05), ischial ratio (r =- 0.49, p < 0.05) and ischial angle (r = -0.55, p < 0.05). The range of external rotation was lower in patients with posterior pelvic tilt (p < 0.05) and in those with a high offset femoral component (p < 0.05) due to posterior bony impingement. Conclusion: Posterior bony impingement after THA is more likely in patients with a wider ischium and a narrow ischiofemoral space. A high femoral offset and posterior pelvic tilt are also risk factors for this type of impingement. Cite this article: Bone Joint J 2017;99-B:1140–6.